The coal and peat of Limón Basin, Costa Rica - Bolaños, Kenneth (2021)
The South Limón basin, located in the Caribbean region of Costa Rica, was investigated in the 1980’s for its coal resources. A detailed geological description and interpretation was made, which included a large number of drilling, with average depths of 200 m. Coal is found in metric layers interbedded in the lower part of the middle member of the geological unit which is known as the Río Banano Formation, whose age varies from the Upper Miocene to the Pliocene. It is a sedimentary sequence deposited in a predominantly deltaic environment. From a lithological point of view, it corresponds to claystones, siltstones and sandstones, up to conglomerates. Coal exploration was mainly concentrated in the areas of Zent and Uatsi. Peat deposits were also mapped and described at various locations of Limón basin. In total, around 47 million metric tons of subbituminous coal B and C were evaluated, with a caloric value between 4500 and 5500 kcal / kg, which was estimated to be mined in a combination of underground and open-pit mining. The environmental impact and the coverage of sterile material are two of the most negative characteristics for an eventual exploitation of this resource.